About teaching mathematics : a K-8 resource - Burns, Marilyn, 1941- (Sausalito, Calif. : Math Solutions Publications, 2000)
Provides primary and middle school teachers with the resources and activities needed to teach their students the fundamentals of mathematics.
Includes bibliographical references (p. 311-315) and index.
Professional
Keywords: Mathematics -- Study and teaching (Elementary); Teaching -- Aids and devices; Mathematics -- Study and teaching; Teaching -- Aids and devices